2014
DOI: 10.5430/jnep.v4n3p252
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of a visiting scholar program between Brazil and Canada

Abstract: Background: International experiences provide a rich, transformative learning opportunity and are fundamental to the internationalization of universities that is occuring globally. To date there has been limited research to evaluate the experiences of, and benefits to, faculty members who participate in an international experience. In the current paper, we report findings from the evaluation of a Visiting Scholar Program (VSP) between the University of São Paulo at Ribeirão Preto College of Nursing (EERP-USP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The literature focusing on visiting doctoral programs has reported that an appropriate time window is required to enable PhD students to adapt to a new culture and often language, and to a home life abroad, before they are able to start working effectively. Only after they have adapted can they start developing working relationships and actively participate in the life of the hosting university (Mill, Johnson, et al, 2014). In detail, our findings show that increasing the visiting period by 1 year improves the probability of establishing a first-stage cross-border collaboration by 21 pp (Model 1, Table 7).…”
Section: Resultsmentioning
confidence: 76%
“…The literature focusing on visiting doctoral programs has reported that an appropriate time window is required to enable PhD students to adapt to a new culture and often language, and to a home life abroad, before they are able to start working effectively. Only after they have adapted can they start developing working relationships and actively participate in the life of the hosting university (Mill, Johnson, et al, 2014). In detail, our findings show that increasing the visiting period by 1 year improves the probability of establishing a first-stage cross-border collaboration by 21 pp (Model 1, Table 7).…”
Section: Resultsmentioning
confidence: 76%
“…An activities, contributing to solidifying the partnership (7) . Joint writing of scientific papers for publication between the FON and EERP-USP scholars was experienced as very positive.…”
Section: Case Examplementioning
confidence: 99%
“…Furthermore, considering that there is limited research to describe the benefits and challenges of international programs for nursing faculty, this article focuses on the cross-cultural experiences and the development of intercultural competencies described by scholars and supervisors involved with the VSP nursing program in Canada and Brazil. Findings related to the scholarly outcomes of participation in the VSP have been published elsewhere (Mill, Johnson, Mendes, Ventura, & Brito, 2014).…”
Section: Aimmentioning
confidence: 99%